2022
DOI: 10.21608/erjm.2022.111710.1132
|View full text |Cite
|
Sign up to set email alerts
|

Forced Convection From an Isothermal Circular Cylinder Rotating Steadily in a Cross Stream of Nanofluid

Abstract: In this paper forced convection from steady rotating circular cylinder in a cross stream of nanofluid is theoretically investigated. The nanofluid is formed by adding Nanometric particles of copper to water. The flow and energy governing equations are solved using Fourier spectral method. The main influencing parameters on flow and thermal fields are Reynolds number, particles volume fraction and the cylinder speed ratio (peripheral velocity of rotating cylinder/ uniform free stream velocity). The Reynolds num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study deduced that the local Nusselt number is found to be increased with increasing solid volume fraction of nanoparticles and with axis ratio increasing. Apart from elliptic cylinders, numerical study of forced convection from a steady rotating circular cylinder in a nanofluid flow has been carried out by Mahfouz et al [12]. The Reynolds number is considered up to 200, and the volume fraction of nanoparticles is up to 5%.…”
Section: Introductionmentioning
confidence: 99%
“…The study deduced that the local Nusselt number is found to be increased with increasing solid volume fraction of nanoparticles and with axis ratio increasing. Apart from elliptic cylinders, numerical study of forced convection from a steady rotating circular cylinder in a nanofluid flow has been carried out by Mahfouz et al [12]. The Reynolds number is considered up to 200, and the volume fraction of nanoparticles is up to 5%.…”
Section: Introductionmentioning
confidence: 99%